High-temperature liquid antimony electrode sealing material

By using glass glue in the form of oxide containing specific elements as the sealing material for liquid antimony anode batteries, a dense intermediate layer is generated and triggered repair capabilities are provided, and the problems of poor sealing effect and prone to cracking in the prior art are solved, thereby achieving better sealing effect and long-term operation capabilities.

CN119833670AActive Publication Date: 2025-04-15XIAN ZHONGBIAN NEW ENERGY TECH CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510139677.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-15
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

In the prior art, when ceramic glue is used as a sealing material in liquid antimony anode SOFC, the sealing effect can only last for dozens of hours, and conventional glass glue is prone to cracking at high temperatures, which cannot meet the sealing needs of high-temperature liquid batteries that run for a long time.

Method used

Glass glue in the form of oxides containing sodium, potassium, calcium, magnesium, boron, barium, iron or cerium is used as the battery sealing material. This material generates a dense intermediate layer in the liquid antimony anode battery and has trigger repair capabilities to prevent leakage of antimony metal.

Benefits of technology

It achieves a better sealing effect, meets the long-term operation needs of liquid metal batteries, and further enhances the self-repairing ability of sealing materials through trigger repair function, avoiding further leakage of antimony metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005264410470000051
    Figure BDA0005264410470000051
  • Figure HDA0005264410480000011
    Figure HDA0005264410480000011
  • Figure HDA0005264410480000012
    Figure HDA0005264410480000012
Patent Text Reader

Abstract

The invention provides a high-temperature liquid antimony electrode sealing material. The sealing material is glass cement containing one or more of a sodium element, a potassium element, a calcium element, a magnesium element, a boron element, a barium element, an iron element or a cerium element. The sealing material not only can generate a more compact middle layer in the operation process of the liquid antimony anode battery, but also can generate trigger type repair with leaked antimony to prevent further leakage of antimony metal, so that a better sealing effect can be achieved, and the long-time operation of the liquid metal battery is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery materials, and in particular, relates to a high-temperature liquid antimony electrode sealing material. Background Art

[0002] Ceramic glue is a common high-temperature sealing material and is widely used in the sealing of solid oxide fuel cells (SOFCs). The main component of ceramic glue is aluminosilicate, which has good insulation and corrosion resistance. Although there are many pores inside the sintered ceramic glue structure, the surface tension between the liquid antimony metal and the main component of the ceramic glue, aluminosilicate, is large, so it is difficult for liquid antimony in the liquid antimony anode SOFC to penetrate through these micropores. Therefore, in previous liquid antimony anode SOFCs, ceramic glue was used as the first choice for sealing materials.

[0003] As the battery runs, the antimony oxide generated causes the surface tension of the antimony metal-ceramic glue to decrease, and then penetrates into the micropores of the ceramic glue, causing corrosion. Therefore, the use of ceramic glue for sealing in liquid antimony metal can only guarantee a sealing effect for tens of hours, and a more suitable sealing material and sealing structure are needed. Summary of the invention

[0004] The inventors found that conventional glass glue as a liquid phase high temperature sealing material has excellent density, but during the operation of the battery, antimony, antimony oxide and glass glue are all liquid, and the density of glass glue is the smallest. Therefore, under the action of gravity, the denser antimony and antimony oxide will pass through the glass glue sealing area, causing leakage. To this end, the present invention proposes a glass glue with excellent sealing properties for liquid antimony anode batteries.

[0005] In the first aspect of the present invention, the present invention proposes a battery sealing material. According to an embodiment of the present invention, the sealing material is a glass glue containing one or more of sodium, potassium, calcium, magnesium, boron, barium, iron or cerium. The inventors found that there are a large number of voids inside the traditional battery sealing material ceramic glue, which is not suitable for high-temperature liquid batteries that run for a long time, and conventional glass glue has the problem of cracking under long-term operation. However, according to the embodiment of the present invention, the glass glue containing one or more of the elements, potassium, calcium, magnesium, boron, barium, iron or cerium will not only generate a denser intermediate layer during the operation of the liquid antimony anode battery, but also can trigger repair with the leaking antimony to prevent further leakage of antimony metal, thereby achieving a better sealing effect and meeting the long-term operation of the liquid metal battery.

[0006] According to an embodiment of the present invention, the battery sealing material may further include at least one of the following additional technical features:

[0007] According to an embodiment of the present invention, the elements exist in the form of oxides.

[0008] According to an embodiment of the present invention, the sodium element exists in the form of Na2SiO3.

[0009] According to an embodiment of the present invention, the potassium element exists in the form of K2SiO3.

[0010] According to an embodiment of the present invention, the calcium element exists in the form of CaO.

[0011] According to an embodiment of the present invention, the magnesium element exists in the form of MgO.

[0012] According to an embodiment of the present invention, the boron element exists in the form of B2O3.

[0013] According to an embodiment of the present invention, the barium element exists in the form of BaO. The inventors found that BaO reacts with liquid antimony to generate a solid phase mixture of Ba3Sb4O and Ba3Sb2O6, forming a dense intermediate layer to block the leakage of liquid antimony metal. When liquid antimony leaks, a triggered repair will occur at the leak, that is, the Sb2O3 that invades the crack will also cause the BaO in the glass to segregate, generating solid phase BaSb2O6 in the pores, thereby achieving a sealed self-repairing effect.

[0014] According to an embodiment of the present invention, the iron element exists in the form of Fe2O3. The inventors found that Fe2O3 reacts with liquid antimony to generate a solid phase mixture of FeO and FeSb2O4, forming a dense intermediate layer to block the leakage of liquid antimony metal.

[0015] According to an embodiment of the present invention, the cerium element exists in the form of CeO2. The inventors have found that CeO2 reacts with liquid antimony to generate Ce2O3 and Ce3Sb5O 12 The solid phase mixture forms a dense intermediate layer, which blocks the leakage of liquid antimony metal.

[0016] According to an embodiment of the present invention, the sealing material is glass glue containing one or more of barium, iron or cerium.

[0017] According to an embodiment of the present invention, the elements exist in the form of oxides.

[0018] According to an embodiment of the present invention, the barium element exists in the form of BaO. The inventors found that BaO reacts with liquid antimony to generate a solid phase mixture of Ba3Sb4O and Ba3Sb2O6, forming a dense intermediate layer to block the leakage of liquid antimony metal. When liquid antimony leaks, a triggered repair will occur at the leak, that is, the Sb2O3 that invades the crack will also cause the BaO in the glass to segregate, generating solid phase BaSb2O6 in the pores, thereby achieving a sealed self-repairing effect.

[0019] According to an embodiment of the present invention, the iron element exists in the form of Fe2O3. The inventors found that Fe2O3 reacts with liquid antimony to generate a solid phase mixture of FeO and FeSb2O4, forming a dense intermediate layer to block the leakage of liquid antimony metal.

[0020] According to an embodiment of the present invention, the cerium element exists in the form of CeO2. The inventors have found that CeO2 reacts with liquid antimony to generate Ce2O3 and Ce3Sb5O 12 The solid phase mixture forms a dense intermediate layer, which blocks the leakage of liquid antimony metal.

[0021] According to an embodiment of the present invention, the sealing material is a glass glue containing one or more of BaO, Fe2O3 or CeO2. The inventors found that BaO, Fe2O3 or CeO2 can react not only with Sb2O3 but also with Sb to generate a solid phase mixture, forming a dense intermediate layer to block the leakage of liquid antimony metal.

[0022] According to an embodiment of the present invention, the sealing material is glass glue containing BaO. The inventors found that BaO reacts with liquid antimony to generate a solid phase mixture of Ba3Sb4O and Ba3Sb2O6, forming a dense intermediate layer to block the leakage of liquid antimony metal. When liquid antimony leaks, a triggered repair will occur at the leak, that is, the Sb2O3 that invades the crack will also cause the BaO in the glass to segregate, generating solid phase BaSb2O6 in the pores, thereby achieving a sealing self-repairing effect.

[0023] In another aspect of the present invention, the present invention also proposes the application of the aforementioned battery sealing material in solid oxide fuel cells. The inventors have found that there are a large number of voids inside the traditional battery sealing material ceramic glue, which is not suitable for high-temperature liquid batteries that run for a long time. In addition, the conventional glass glue with a higher density of antimony and antimony oxide will pass through the glass glue sealing area under long-term operation, causing leakage. The battery sealing material according to the embodiment of the present invention will not only generate a denser intermediate layer during the operation of the liquid antimony anode battery, but also trigger repair with the leaking antimony to prevent further leakage of antimony metal, thereby achieving a better sealing effect and meeting the long-term operation of the liquid metal battery. Therefore, it can be well applied to solid oxide fuel cells.

[0024] According to an embodiment of the present invention, the above application may further include at least one of the following additional technical features:

[0025] According to an embodiment of the present invention, the solid oxide fuel cell is a high temperature liquid antimony metal battery.

[0026] According to an embodiment of the present invention, the battery sealing material mentioned above is filled in the gap between the anode housing and the half-cell plate of the battery, so as to ensure that the gap between the half-cell plate and the anode housing is completely filled with the battery sealing material mentioned above, so as to enhance the sealing performance of the battery.

[0027] According to an embodiment of the present invention, the filling is performed in the following manner:

[0028] S1: Place an antimony block on the half-cell plate, apply the aforementioned battery sealing material to the edge of the anode shell, place the cover on top of the antimony block and compact it, and further apply the aforementioned battery sealing material on the contact interface between the anode shell and the half-cell plate to form a single cell. This ensures that the gap between the half-cell plate and the anode shell is completely coated with the aforementioned battery sealing material to enhance the sealing of the battery.

[0029] According to an embodiment of the present invention, it further comprises: S2: vertically stacking between the single cells and further compacting with a clamp. Applying silver paste on the ribs of the single cells can ensure better conductivity between the cells. The compaction operation can ensure that the battery sealing material mentioned above completely fills the gap at the contact interface between the anode shell and the half-cell plate. In addition, the compaction operation can also make the upper cathode plate and the lower anode shell in close contact, so that the batteries are better conductive.

[0030] According to an embodiment of the present invention, the area of ​​the single cell is 4 cm 2 -10000cm 2 .

[0031] According to an embodiment of the present invention, the number of the stacks is 2-100.

[0032] According to an embodiment of the present invention, the method further comprises: S3: connecting the ribs of the single cells at the top of the battery stack via metal strips to achieve parallel connection between the stacked single cells.

[0033] According to an embodiment of the present invention, the number of parallel connections is 2-100. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0035] Figure 1 It is a diagram of the repair mechanism of the preferred glass glue, where (a) direct contact with Sb2O3, (b) Sb2O3 intrusion into the crack;

[0036] Figure 2 This is a schematic diagram of a preferred glass glue battery stack;

[0037] Figure 3 This is the SEM image and element distribution map of the barium-containing glass glue antimony metal contact interface;

[0038] Figure 4 The SEM image and element distribution map of the ceramic-antimony-metal contact interface; and

[0039] Figure 5 This is a typical channel diagram of antimony metal leakage in a high-temperature liquid battery prepared using the steps of Comparative Example 2 in a high-temperature environment of 750°C. DETAILED DESCRIPTION

[0040] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0041] Example 1

[0042] The triggers for the triggered repair of the seal of the liquid antimony anode battery are Sb and Sb2O3, so it is necessary to screen sealing materials that can react with Sb and Sb2O3. Existing high-temperature insulating sealing materials are mainly composed of oxides of elements such as aluminum, silicon, sodium, potassium, calcium, magnesium, boron, and barium. However, there is currently almost no research on the reaction characteristics of the oxides of these elements with Sb / Sb2O3. In order to conduct preliminary material screening, the stable composition of Sb / Sb2O3 after reacting with these oxides was calculated based on the Open Quantum Materials Database (OQMD). The calculation was based on the common element existence form in the sealant. In the calculation conditions, the atomic ratio of antimony to other elements was set to 1:1. The calculation results are shown in Table 1 (unconsumed reactants are not listed as reaction products). It can be seen from the calculation results that silicon, aluminum, and zirconium have the strongest stability and do not react with Sb / Sb2O3. This is also an important reason why silicon, aluminum, and zirconium have become the primary components of many sealing materials. In addition to silicon and aluminum, oxides or silicates of various elements commonly used in sealing materials may react with Sb2O3, among which BaO, Fe2O3 and CeO2 can react not only with Sb2O3 but also with Sb to generate solid phase mixtures. This provides a screening range for further optimization of the sealing material system in the future.

[0043] Table 1 Stable existence forms of different elements mixed with Sb / Sb2O3

[0044]

[0045] like Figure 1 As shown in (a), at the working temperature, the BaO preferred glass glue reacts with the liquid antimony to produce a solid phase mixture of Ba3Sb4O and Ba3Sb2O6, forming a dense intermediate layer to block the leakage of liquid antimony metal. In addition, Figure 1 As shown in (b), when liquid antimony leaks, a triggered repair will occur at the leaking site, that is, the Sb2O3 that invades the crack will also cause the BaO in the glass to segregate, generating solid BaSb2O6 in the pores, thereby achieving a sealed self-repairing effect. Similarly, other preferred glass glues have the same sealing effect, which can effectively prevent antimony metal leakage, laying the foundation for the development of high-temperature liquid antimony metal batteries.

[0046] Example 2

[0047] S1: The support body has a length of 100 mm, a width of 100 mm, and a thickness of 1.5 mm.

[0048] S2: The solid antimony metal anode has a mass of 200 g and a size of 80 mm × 80 mm × 5 mm.

[0049] S3: The main shell of the anode housing is in the shape of a lid, with a length of 88 mm, a width of 88 mm, a height of 11 mm and a wall thickness of 3 mm.

[0050] S4: Apply the preferred glass glue (purchased from Ningbo Suofer Energy Technology Co., Ltd., model CY-S) to the bottom edge of the anode shell and cover the antimony block, so that the gap between the anode shell and the support is filled with the preferred glass glue.

[0051] S5: Apply a large amount of preferred glass glue on the outer side of the contact surface between the anode shell and the support body.

[0052] S6: 5 single cells are connected in series to form a battery stack, and 2 battery stacks are connected in parallel.

[0053] S7: Use a fixture to squeeze the battery stack so that the glass glue fills the gap between the anode shell and the support body, and the single cells are in close contact with each other for better conductivity, and the preferred glass glue is distributed more evenly, such as Figure 2 shown.

[0054] The experimental test showed that the high-temperature liquid battery prepared by the above process steps can operate stably at a high temperature of 750°C, and no block antimony metal leakage was found in the glass area. Figure 3 shown.

[0055] Example 3

[0056] S1: The support body has a length of 200 mm, a width of 200 mm, and a thickness of 1.5 mm.

[0057] S2: The solid antimony metal anode has a mass of 400 g and a size of 160 mm × 160 mm × 5 mm.

[0058] S3: The main shell of the anode housing is in the shape of a lid, with a length of 176 mm, a width of 176 mm, a height of 11 mm and a wall thickness of 3 mm.

[0059] S4: Apply the preferred glass glue (purchased from Shanghai Silicate Research Institute, model SG-DB05) to the bottom edge of the anode shell and cover the antimony block, so that the gap between the anode shell and the support is filled with the preferred glass glue.

[0060] S5: Apply a large amount of preferred glass glue on the outer side of the contact surface between the anode shell and the support body.

[0061] S6: 5 single cells are connected in series to form a battery stack, and 2 battery stacks are connected in parallel.

[0062] S7: Use a clamp to squeeze the battery stack so that the glass glue fills the gap between the anode shell and the support body, and the close contact between the single cells has better conductivity and the glass glue is distributed more evenly.

[0063] Experimental tests have shown that the high-temperature liquid battery prepared using the above process steps can operate stably in a high-temperature environment of 750°C without any antimony metal leakage.

[0064] Embodiment 4:

[0065] S1: The support body has a length of 100 mm, a width of 100 mm, and a thickness of 1.5 mm.

[0066] S2: The solid antimony metal anode has a mass of 200 g and a size of 80 mm × 80 mm × 5 mm.

[0067] S3: The main shell of the anode housing is in the shape of a lid, with a length of 88 mm, a width of 88 mm, a height of 11 mm and a wall thickness of 3 mm.

[0068] S4: Apply the preferred glass glue (purchased from Shanghai Silicate Research Institute, model SG-DB05) to the bottom edge of the anode shell and cover the antimony block, so that the gap between the anode shell and the support is filled with the preferred glass glue.

[0069] S5: Apply a large amount of preferred glass glue on the outer side of the contact surface between the anode shell and the support body.

[0070] S6: 20 single cells are connected in series to form a battery stack, and 4 battery stacks are connected in parallel. The distance between the parallel battery stacks is 5 mm.

[0071] S7: Use a clamp to squeeze the battery stack so that the glass glue fills the gap between the anode shell and the support body, reduces the gap between the anode shell and the support body, and makes the single cells in close contact with each other for better conductivity and more evenly distributed glass glue.

[0072] Experimental tests have shown that the high-temperature liquid battery prepared using the above process steps can operate stably in a high-temperature environment of 750°C, and no leakage of bulk antimony metal was found in the glass area.

[0073] Comparative Example 1

[0074] S1: The support body has a length of 100 mm, a width of 100 mm, and a thickness of 1.5 mm.

[0075] S2: The solid antimony metal anode has a mass of 200 g and a size of 80 mm × 80 mm × 5 mm.

[0076] S3: The main shell of the anode housing is in the shape of a lid, with a length of 88 mm, a width of 88 mm, a height of 11 mm and a wall thickness of 3 mm.

[0077] S4: Ceramic glue (purchased from AREMCO, model 552, the main component of which is aluminum oxide) is applied to the bottom edge of the anode shell and covered on the antimony block, so that the gap between the anode shell and the support is filled with the ceramic glue.

[0078] S5: Apply a large amount of ceramic glue on the outside of the contact surface between the anode casing and the support.

[0079] S6: 5 single cells are connected in series to form a battery stack, and 2 battery stacks are connected in parallel.

[0080] S7: Use a clamp to squeeze the battery stack to reduce the gap between the anode casing and the support.

[0081] According to experimental tests, after the high-temperature liquid battery prepared by the above process steps was cycled for 1 hour at 750℃, a large amount of metal penetrated into the pores of the ceramic glue and the pore size of the ceramic glue was expanded, indicating that the structure of the ceramic glue was significantly destroyed by the liquid antimony anode, resulting in sealing failure. Figure 4 shown.

[0082] Comparative Example 2

[0083] S1: The support body has a length of 100 mm, a width of 100 mm, and a thickness of 1.5 mm.

[0084] S2: The solid antimony metal anode has a mass of 200 g and a size of 80 mm × 80 mm × 5 mm.

[0085] S3: The main shell of the anode housing is in the shape of a lid, with a length of 88 mm, a width of 88 mm, a height of 11 mm and a wall thickness of 3 mm.

[0086] S4: conventional glass glue (purchased from Ningbo Suofer Energy Technology Co., Ltd., model CY-S) is applied to the bottom edge of the anode shell and covered on the antimony block, so that the gap between the anode shell and the support is filled with conventional glass glue.

[0087] S5: Apply a large amount of conventional glass glue on the outside of the contact surface between the anode shell and the support.

[0088] S6: 5 single cells are connected in series to form a battery stack, and 2 battery stacks are connected in parallel.

[0089] S7: Use a clamp to squeeze the battery stack, reduce the gap between the anode shell and the support, and distribute the glass glue more evenly.

[0090] After 20 hours of experimental testing, the high-temperature liquid battery prepared by the above process steps showed a typical channel for antimony metal leakage in a high-temperature environment of 750°C. Figure 5 As shown, a large amount of antimony metal leakage occurred and the seal failed.

[0091] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0092] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A battery sealing material, characterized in that: The sealing material is glass glue containing one or more of sodium, potassium, calcium, magnesium, boron, barium, iron or cerium.

2. The battery sealing material according to claim 1, characterized in that The elements are present in the form of oxides; Optionally, the sodium element exists in the form of Na2SiO3; Optionally, the potassium element exists in the form of K2SiO3; Optionally, the calcium element exists in the form of CaO; Optionally, the magnesium element exists in the form of MgO; Optionally, the boron element exists in the form of B2O3; Optionally, the barium element is present in the form of BaO; Optionally, the iron element exists in the form of Fe2O3; Optionally, the cerium element exists in the form of CeO2.

3. The battery sealing material according to claim 1, characterized in that The sealing material is glass glue containing one or more of barium, iron or cerium elements; Optionally, the element is present in oxide form; Optionally, the barium element is present in the form of BaO; Optionally, the iron element exists in the form of Fe2O3; Optionally, the cerium element exists in the form of CeO2.

4. The battery sealing material according to claim 1, characterized in that The sealing material is glass glue containing one or more of BaO, Fe2O3 or CeO2; Optionally, the sealing material is glass glue containing BaO.

5. Use of the battery sealing material according to any one of claims 1 to 4 in a solid oxide fuel cell.

6. The use according to claim 5, characterized in that: The solid oxide fuel cell is a high temperature liquid antimony metal battery.

7. The use according to claim 5 or 6, characterized in that: include: The battery sealing material according to any one of claims 1 to 4 is used to fill the gap between the anode casing and the half cell plate of the battery.

8. The use according to claim 7, characterized in that: The filling is carried out in the following manner: S1: Place an antimony block on the half-cell plate, apply the battery sealing material described in any one of claims 1 to 4 to the edge of the anode shell, then place a cover on the antimony block and compact it, and further apply the battery sealing material described in any one of claims 1 to 4 to the contact interface between the anode shell and the half-cell plate to form a single cell.

9. The use according to claim 8, characterized in that: Further including: S2: vertically stacking the cells and further compacting them using a clamp; Optionally, the area of ​​the single cell is 4 cm 2 -10000cm 2 ; Optionally, the number of the stacks is 2-100.

10. The use according to claim 9, characterized in that: Further including: S3: connecting the ribs of the single cells at the top of the battery stack through metal strips to achieve parallel connection between the stacked single cells; Optionally, the number of parallel connections is 2-100.

Citation Information

Patent Citations

  • Sealing material of medium temperature plate type solid-oxide fuel battery stack and sealing method

    CN102723448A

  • Solid oxide fuel cell composite sealant and application thereof

    CN109841868A

  • Novel high-temperature composite sealing material and application thereof

    CN112928299A

  • Battery monomer, liquid metal air battery with battery monomer and electric equipment

    CN118572266A

  • Glassy or at least semi-crystalline joining material and its use as well as joining connection

    DE102013209970B3